Self-care behaviour and blood glucose control in young adults with type 1 diabetes mellitus. - Peveler, R; Davies, B; Mayou, R; Fairburn, C; Mann, J (1993)
Self-care behaviour, knowledge about diabetes, and blood glucose control were studied in 113 young adults with Type 1 diabetes using a semi-structured interview, self-report questionnaires, and a biochemical measure (glycated haemoglobin). The majority of subjects followed their prescribed regimen reasonably accurately, but individuals followed different aspects of the regimen to different degrees. Subjects were more concerned with the avoidance of hypoglycaemia than with attainment of 'tight' blood glucose control. The blood glucose test level at which subjects took remedial action was the best single predictor of symptomatic control. Frequency of nocturnal polyuria appeared to be a reliable indicator of impaired metabolic control. Insulin omission or dose reduction for the purpose of body weight reduction was common among women, who also had worse blood glucose control than men. Elevated glycated haemoglobin levels were associated with higher alcohol consumption in men. Theoretical knowledge about diabetes management was only weakly associated with self-care behaviour and blood glucose control in this population. The blood glucose test result at which subjects take remedial action appears to be the most appropriate behavioural target for intervention to improve control in such subjects.